2013
DOI: 10.1097/dcr.0b013e3182919093
|View full text |Cite
|
Sign up to set email alerts
|

D3 Lymph Node Dissection in Right Hemicolectomy with a No-touch Isolation Technique in Patients With Colon Cancer

Abstract: D3 lymphadenectomy with a no-touch isolation technique allows curative resection and long-term survival in a cohort of patients with cancer of the right colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
49
2
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(67 citation statements)
references
References 34 publications
7
49
2
9
Order By: Relevance
“…In addition to CME, radical lymphadenectomy, comprising apical lymph nodes, proper of CVL, is of paramount importance in obtaining adequate regional control and impact on survival: the latest 2010 Japanese Society for Cancer of the Colon and Rectum (JSCCR) guidelines recommend D2 dissection for clinically early stages of colorectal cancers and D3 dissection for more advanced disease, reaching impressive results in terms of local recurrence and patients' survival (23,24); yet, similar results have also been reported by Western authors, who claim CME with CVL as oncologically effective for right colonic cancer as D3 right hemicolectomy performed in Eastern countries (8,25,26). In fact, even if not yet completely established, CVL is crucial in micrometastatic clearance of central nodes, which are frequently missed by routine histological examination (27) and thus responsible for locoregional recurrence and systemic dissemination (24); furthermore, for cancers located in the hepatic flexure and proximal transverse colon, there is a metastatic nodes incidence of about 5% for subpyloric station and about 4% for right gastroepiploic arcade (28): thus, central transection of middle colic vessels, ligation of right gastroepiploic vessels at the origin, 10-15 cm of greater omentectomy off the tumor, and removal of subpyloric nodes are all mandatory, especially in advanced stages (8).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CME, radical lymphadenectomy, comprising apical lymph nodes, proper of CVL, is of paramount importance in obtaining adequate regional control and impact on survival: the latest 2010 Japanese Society for Cancer of the Colon and Rectum (JSCCR) guidelines recommend D2 dissection for clinically early stages of colorectal cancers and D3 dissection for more advanced disease, reaching impressive results in terms of local recurrence and patients' survival (23,24); yet, similar results have also been reported by Western authors, who claim CME with CVL as oncologically effective for right colonic cancer as D3 right hemicolectomy performed in Eastern countries (8,25,26). In fact, even if not yet completely established, CVL is crucial in micrometastatic clearance of central nodes, which are frequently missed by routine histological examination (27) and thus responsible for locoregional recurrence and systemic dissemination (24); furthermore, for cancers located in the hepatic flexure and proximal transverse colon, there is a metastatic nodes incidence of about 5% for subpyloric station and about 4% for right gastroepiploic arcade (28): thus, central transection of middle colic vessels, ligation of right gastroepiploic vessels at the origin, 10-15 cm of greater omentectomy off the tumor, and removal of subpyloric nodes are all mandatory, especially in advanced stages (8).…”
Section: Discussionmentioning
confidence: 99%
“…43 Reports from Japan focusing on CVL also showed impressive results from D3 lymphadenectomy. 44,45 In their systematic review, Killeen et al reported 5-year local recurrence rate, overall survival rate, and disease-free survival rate of 4.5%, 58.1%, and 77.4%, respectively. 46 However, studies comparing laparoscopic excision to open CME raised issues regarding the completeness of laparoscopic excision for tumors near the flexures or in the transverse colon.…”
mentioning
confidence: 99%
“…Other studies advocate that there are three separate components defining the optimal CME surgery: the first one refers to the preservation of the integrity of the mesocolic plane during dissection, the second one refers to the central ligation of the tumor feeding blood vessel while the third refers to the removal of an appropriate length of large bowel on both sides of the tumor [12]. However, while the first component is widely accepted, the other two references have been contested by some authors: although some authors strongly sustain the benefits of central vein ligation [13,14], other studies show no difference between high and low ligation [15,16]. As for the length of removed colon, the Japanese studies propose alternative principles regarding the amount of normal colon resected [17].…”
Section: The Concept Of Complete Mesocolic Excisionmentioning
confidence: 97%